2022
DOI: 10.3390/molecules27030943
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anticancer Activity of the Furanocoumarin Derivative Xanthotoxin Isolated from Ammi majus L. Fruits: In Vitro and In Silico Studies

Abstract: Ammi majus L., an indigenous plant in Egypt, is widely used in traditional medicine due to its various pharmacological properties. We aimed to evaluate the anticancer properties of Ammi majus fruit methanol extract (AME) against liver cancer and to elucidate the active compound(s) and their mechanisms of action. Three fractions from AME (Hexane, CH2Cl2, and EtOAc) were tested for their anticancer activities against HepG2 cell line in vitro (cytotoxicity assay, cell cycle analysis, annexin V-FITC apoptosis assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…The disparities between normal and cancer cells' reactions to xanthotoxin may be explained by one of the most distinguishing characteristics of cancer cells over those of normal cells 26 : increased expression of the relaxing enzyme topoisomerase II 27,28 . Finally, all these effects of plant are summarized as follow: ammi majus secondary metabolite possesses the capacity to stimulate the function of the immune system, inhibit the formation of DNA adduct with carcinogens, inhibit hormonal action and metabolic pathways associated with the development of cancer and enhance the phase I or II detoxification enzymes 29,30. Furthermore, investigations have shown that terpenoids may increase tumor latency and decrease tumor multiplicity 31 .…”
Section: Bone Marrow Mitotic Index Of Male Albino Micementioning
confidence: 99%
“…The disparities between normal and cancer cells' reactions to xanthotoxin may be explained by one of the most distinguishing characteristics of cancer cells over those of normal cells 26 : increased expression of the relaxing enzyme topoisomerase II 27,28 . Finally, all these effects of plant are summarized as follow: ammi majus secondary metabolite possesses the capacity to stimulate the function of the immune system, inhibit the formation of DNA adduct with carcinogens, inhibit hormonal action and metabolic pathways associated with the development of cancer and enhance the phase I or II detoxification enzymes 29,30. Furthermore, investigations have shown that terpenoids may increase tumor latency and decrease tumor multiplicity 31 .…”
Section: Bone Marrow Mitotic Index Of Male Albino Micementioning
confidence: 99%
“…8‐MOP can increase the content of phosphorylated Chk1 and decrease the proportion of phosphorylated cdc2 (Sumiyoshi, Sakanaka, Taniguchi, Baba, & Kimura, 2014). They assayed the cytotoxicity of XAT with HepG2 cells and showed that XAT had strong cytotoxic activity against HepG2 cells (IC 50 = 6.9 ± 1.07 μg/mL), then HepG2 cells were treated with 6.9 μg/mL of XAT and cell cycle was observed, which showed significant changes in cell cycle (increase in G1 and G2/M phases and decrease in s phase), XAT induced a significant increase in Annexin‐v‐positive HepG2 cells in the early and late stages of apoptosis compared to controls, along with a significant decrease in autophagy in cancer cells (Issa et al, 2022). Inflammatory signaling pathways are intimately related to cancer.…”
Section: Pharmacological Effects Of Xanthotoxinmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32] Coumarin derivatives can also be used as fluorescence markers or imaging agents to identify tumor lesions and study the subcellular localization of drugs. [33][34][35][36][37][38][39][40][41][42][43][44] The development of a sensor with high selectivity and sensitivity to copper ions remains an important challenge. In this paper, two novel fluorescent probes were synthesized using coumarin with an aldehyde (CHO group) as the fluorophore.…”
Section: Introductionmentioning
confidence: 99%